2017
DOI: 10.1158/2326-6066.cir-16-0374
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with High-Affinity Epitopes Impairs Antitumor Efficacy by Increasing PD-1 Expression on CD8+ T Cells

Abstract: Antitumor vaccines encoding self-antigens generally have low immunogenicity in clinical trials. Several approaches are aimed at improving vaccine immunogenicity, including efforts to alter encoded epitopes. Immunization with epitopes altered for increased affinity for the major histocompatibility complex (MHC) or T-cell receptor (TCR) elicits greater numbers of CD8 T cells but inferior antitumor responses. Our previous results suggested that programmed death 1 (PD-1) and its ligand (PD-L1) increased on antigen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 55 publications
2
65
0
Order By: Relevance
“…The current trial sought to determine if combining anti-tumor vaccination with PD-1 blockade might be synergistic. This was based on preclinical studies demonstrating that the anti-tumor efficacy of DNA vaccines could be increased with PD-1 blockade employed at the time of PD-1 upregulation that occurs with vaccine-mediated T-cell activation [ 17 , 18 ], and that PD-1 regulated T-cell immunity occurred in patients previously treated with a DNA vaccine encoding PAP [ 19 ]. To our knowledge, this is one of the first reports of a clinical trial using an anti-tumor vaccine in combination with PD-1 blockade, and the first report using a DNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current trial sought to determine if combining anti-tumor vaccination with PD-1 blockade might be synergistic. This was based on preclinical studies demonstrating that the anti-tumor efficacy of DNA vaccines could be increased with PD-1 blockade employed at the time of PD-1 upregulation that occurs with vaccine-mediated T-cell activation [ 17 , 18 ], and that PD-1 regulated T-cell immunity occurred in patients previously treated with a DNA vaccine encoding PAP [ 19 ]. To our knowledge, this is one of the first reports of a clinical trial using an anti-tumor vaccine in combination with PD-1 blockade, and the first report using a DNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…We found that efforts to increase the magnitude of immune response by encoding epitopes with greater MHC class I affinity led to inferior anti-tumor efficacy in tumor-bearing mice [ 17 ]. This was due to the expression of PD-1 on antigen-specific CD8+ T cells elicited with immunization, and blockade of PD-1 or PD-L1 at the time of T-cell activation with immunization led to superior anti-tumor efficacy [ 17 , 18 ]. In other preclinical studies, we found that patients previously immunized with either pTVG-HP or sipuleucel-T developed PD-1-regulated immune responses, and that circulating tumor cells increased expression of PD-L1 after immunization [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“… 33 Another recent study demonstrated that vaccination with altered peptide ligands with optimized CMH or TCR affinity led to a strong but inefficient specific CD8 T cell response, impaired by a sustained expression of PD-1 (and other inhibitory receptors) by stimulated specific T cells. 38 The anti-tumor efficiency of such vaccines could thus be improved through a combination therapy targeting PD-1/PD-L1 signaling pathway.…”
Section: Pd-1 Expression and Anti-tumor Responsementioning
confidence: 99%
“…MuPeXI [60] The extraction and induction of mutant peptides can roughly identify tumor-specific peptides, predict their immunogenicity, and evaluate their potential for new epitopes Based on a pipeline connecting commonly used bioinformatic software via custom python scripts to provide neoantigen burden, tumor heterogeneity, immune stimulation potential and HLA haplotype of patients [68][69][70]. Mutations in tumor cells change the amino acid sequences of proteins, which are then translated and processed into short peptides [71] called tumor neoantigens.…”
Section: Principle Of Neoantigen Vaccinesmentioning
confidence: 99%